2022
DOI: 10.1001/jamanetworkopen.2022.7038
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of Safety of 3 Doses of COVID-19 mRNA Vaccination Using Electronic Health Records

Abstract: This cohort study assesses adverse events associated with a third dose of mRNA COVID-19 vaccine using data from electronic health records (EHRs).

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…Most of our results are consistent with those observed in previous studies that evaluated the safety of the COVID-19 booster [17][18][19]. In the COV-BOOST study, seven different COVID-19 vaccine booster doses were compared for both the BNT162b2 primary series and the ChAdOx1 nCov-19 primary series.…”
Section: Strengths and Weaknesses In Relation To Other Studiessupporting
confidence: 88%
“…Most of our results are consistent with those observed in previous studies that evaluated the safety of the COVID-19 booster [17][18][19]. In the COV-BOOST study, seven different COVID-19 vaccine booster doses were compared for both the BNT162b2 primary series and the ChAdOx1 nCov-19 primary series.…”
Section: Strengths and Weaknesses In Relation To Other Studiessupporting
confidence: 88%
“…Only 41 studies met our inclusion criteria 22,61–100 ; these consisted of 18 case series/reports, 18 cohort studies without control groups, and 4 cohort studies with control groups, one of which was a double‐blinded randomized clinical trial. The last study, Kaplan et al, 79 contained both a cohort analysis and a case series.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search screened 1296 studies of which 102 were reviewed in full text (Figure 1). A total of 43 studies were included in the meta-analyses, of which reported 16,978 cases of myocarditis [7,8,1751] , 28,451 cases of myocardial infarction [8,19,20,43,47,50,5258] and 96,269 cases of cardiac arrhythmia [8,19,21,22,24,43,44] (Table S1). Overall risk of bias in these studies were rated as moderate to high quality (Tables S2 and S3).…”
Section: Resultsmentioning
confidence: 99%